PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN LAMONGAN - ARIS BUDI SUSANTO (Universitas Negeri Surabaya, 2013)
This study examines the influence of HumanDevelopment Indeks( HDI) and inflation on economic growth in regency Lamongan on 2002-201. The purpose of this research are to identified how influence the variables HDI and inflation on economic growth in Lamongan regency. In order to verify research hypothesis the econometric model was used with OLS (Ordinary Least Square) method. From the analysis result could be concluded that IPM variable and inflation based on simultaneous test result, all variables simultaneously have significant effect toward economic growth of Lamongan Keyword: Human Development Indeks(HDI, inflation.